Cathode body and electrolytic capacitor

The cathode body with a conductive layer adjusts its potential to suppress hydrogen gas generation in high-voltage electrolytic capacitors, ensuring capacitor integrity and voltage withstand by favoring dissolved oxygen reduction over hydrogen ions, addressing the hydrogen issue in medium and high-voltage electrolytic capacitors.

CN114616640BActive Publication Date: 2024-12-13NIPPON CHEMI CON CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180005497.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-09-29
Publication Date
2024-12-13
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

Electrolytic capacitors for medium and high voltage applications above 100V, particularly those above 160V and 250V, face significant hydrogen gas generation due to anodic reactions, which can lead to increased internal pressure and reduced withstand voltage when nitro compounds are used to inhibit hydrogen generation, as they degrade over time.

Method used

A cathode body for electrolytic capacitors is designed with a conductive layer on the cathode foil, adjusting its potential to be higher than the natural immersion potential of the reference cathode foil, thereby suppressing hydrogen gas generation by favoring the cathode reaction of reducing dissolved oxygen over hydrogen ions, even in the presence or absence of nitro compounds.

Benefits of technology

The cathode body effectively suppresses hydrogen gas generation, maintaining capacitor integrity and voltage withstand, even at high voltages, by preferentially reducing dissolved oxygen over hydrogen ions, thus enhancing the capacitors' performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114616640B_ABST
    Figure CN114616640B_ABST
Patent Text Reader

Abstract

The present invention provides a cathode body capable of suppressing the generation of hydrogen gas and an electrolytic capacitor including the cathode body. The cathode body of the electrolytic capacitor includes a cathode foil of a valve metal and a conductive layer formed on the surface of the cathode foil. When a current flows in the range of the current density of the leakage current of the electrolytic capacitor due to electrochemical polarization, the potential corresponding to the current is higher than the natural immersion potential of a control cathode foil of the same type as the valve metal and having a purity of 99.99% or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cathode body included in an electrolytic capacitor and the electrolytic capacitor. Background Art

[0002] Electrolytic capacitors include valve metals such as tantalum or aluminum as anode foil and cathode foil. The anode foil is expanded by forming the valve metal into a sintered body or an etched foil, and has a dielectric oxide film layer on the expanded surface. The electrolyte is between the anode foil and the cathode foil. The electrolyte is in close contact with the concave and convex surface of the anode foil and functions as a true cathode.

[0003] The electrolyte repairs the deteriorated parts such as deterioration or damage of the dielectric oxide film formed on the anode foil by leakage current. However, hydrogen gas is generated at the beginning of the film repair of the dielectric oxide film using leakage current. That is, when the film is repaired by leakage current on the anode side, an anode reaction represented by the following chemical reaction formula (1) occurs. Moreover, when the film is repaired by leakage current on the cathode side, electrons generated in the anode reaction are received, and a cathode reaction represented by the following chemical reaction formula (2) in which hydrogen ions are reduced occurs. The atomic hydrogen generated in the chemical reaction formula (2) is bonded as represented by the following chemical reaction formula (3) to generate hydrogen gas.

[0004] 2Al+3H2O→Al2O3+6H + +6e - ……(1)

[0005] 6H + +6e - →6H ad …(2)

[0006] 6H ad →3H2…(3)

[0007] Hydrogen gas will increase the internal pressure of the electrolytic capacitor, which may cause the expansion of the case that contains the capacitor element, the expansion of the sealing body that seals the capacitor element, or the opening of the pressure release valve provided in the electrolytic capacitor. If the leakage current on the anode side increases, the movement of the charge on the electrode surface on the anode side will intensify, and according to Faraday's law, the reaction amount on the cathode side will also increase, and the amount of hydrogen generated on the cathode side will increase.

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] Patent Document 1: Japanese Patent Laid-Open No. 2017-34030 Summary of the invention

[0011] [Problems to be solved by the invention]

[0012] In recent years, electrolytic capacitors are sometimes required to withstand voltages of more than 100V, such as for on-board applications such as electric vehicles or power applications. Therefore, electrolytic capacitors for medium and high voltage applications of more than 100V include an expanded surface layer consisting of multiple tunnel-shaped pits in the anode foil. In addition, the electrolytic capacitor includes an expanded surface layer having tunnel-shaped pits that penetrate the foil on a part or the entire surface of the anode foil. In this way, through the expansion technology, electrolytic capacitors for medium and high voltage applications of more than 100V achieve a large surface area of ​​the anode foil while ensuring the thickness of the dielectric oxide film.

[0013] In the case of requiring further electrostatic capacitance for electrolytic capacitors for medium and high voltage applications above 100V, it is considered to thin the dielectric oxide film. However, if the dielectric oxide film is thinned, the valve metal will be easily in contact with the water in the electrolyte, which will easily cause the anodic reaction represented by the chemical reaction formula (1), resulting in an increase in the amount of hydrogen produced. The generation of hydrogen caused by this anodic reaction is particularly observed in electrolytic capacitors for medium and high voltage applications above 160V, and becomes particularly significant in electrolytic capacitors for medium and high voltage applications above 250V.

[0014] It is also possible to consider adding a nitro compound to the electrolyte. The nitro compound is reduced on the cathode side and reacts with hydrogen ions. Therefore, the nitro compound inhibits the generation of hydrogen. However, depending on the type of nitro compound, the withstand voltage of the electrolytic capacitor decreases, so the amount used is limited. In addition, the nitro compound is reduced on the cathode side over time, and the hydrogen suppression performance decreases.

[0015] Thus, a new method for more effectively suppressing hydrogen gas is required for electrolytic capacitors. The present invention is made to solve the above-mentioned problems, and an object of the present invention is to provide a cathode body capable of suppressing the generation of hydrogen gas and an electrolytic capacitor including the cathode body.

[0016] [Technical means to solve the problem]

[0017] First, the capacitance appearance rate is defined. The capacitance appearance rate is the ratio of the electrostatic capacitance of the electrolytic capacitor to the electrostatic capacitance on the anode side. That is, the so-called capacitance appearance rate is the percentage of the ratio obtained by dividing the composite electrostatic capacitance of the electrolytic capacitor as a capacitor connected in series on the anode side and the cathode side by the electrostatic capacitance on the anode side. The composite electrostatic capacitance is obtained by dividing the multiplication result of the electrostatic capacitance on the anode side and the electrostatic capacitance on the cathode side by the sum of the electrostatic capacitance on the anode side and the electrostatic capacitance on the cathode side. Therefore, the capacitance appearance rate is expressed by the following formula 1.

[0018] (Formula 1)

[0019]

[0020] As shown in Formula 1, when the electrostatic capacitance on the anode side is large, the influence of the cathode side on the capacitance appearance ratio becomes large. On the other hand, when the electrostatic capacitance on the anode side is small, the influence of the cathode side on the capacitance appearance ratio becomes small.

[0021] Here, in the field of electrolytic capacitors, the anode foil for electrolytic capacitors for so-called medium and high voltage applications above 100V has a smaller electrostatic capacitance per unit area than the anode foil for electrolytic capacitors for low voltage applications. The reason is that in the anode foil for electrolytic capacitors for medium and high voltage applications, in order to ensure the withstand voltage, the dielectric oxide film on the surface of the expanded layer becomes thicker. If it is considered from the perspective of increasing the capacitance appearance rate, in electrolytic capacitors in low-voltage areas where the electrostatic capacitance on the anode side is large, in order to increase the capacitance appearance rate, the effect of increasing the capacitance on the cathode side is large. However, in electrolytic capacitors for medium and high voltage applications where the electrostatic capacitance on the anode side is small, even if the electrostatic capacitance on the cathode side is increased, the effect of the capacitance appearance rate is small.

[0022] For example, as a low-voltage electrolytic capacitor, when using 1 cm 2 When the electrostatic capacitance of the anode foil is 10μF, use 2 The capacitance appearance rate is 90.9% when the cathode foil has an electrostatic capacitance of 100μF. 2 The capacitance appearance rate is 99.0% when the electrostatic capacitance reaches 1000μF, and the capacitance appearance rate is expected to increase by 109%. On the other hand, as an electrolytic capacitor for medium and high voltage applications, the capacitance appearance rate is 99.0% when the electrostatic capacitance reaches 1000μF, and the capacitance appearance rate is expected to increase by 109%. 2 The electrostatic capacitance of the anode foil is 1μF, and the 2 The capacitance appearance rate is 99.0% when the cathode foil has an electrostatic capacitance of 100μF. 2 The capacitance appearance rate when the electrostatic capacitance reaches 1000μF is 99.9%, and the capacitance appearance rate is almost not improved.

[0023] In electrolytic capacitors for medium and high voltage applications, where the effect of capacitance appearance ratio is small even if the electrostatic capacitance on the cathode side is increased, the operation of forming a conductive layer on the cathode foil surface for the purpose of increasing the surface area is not performed in consideration of the increase in the number of steps.

[0024] On the other hand, the inventors have made intensive studies and have found that hydrogen generation can be suppressed simply by adjusting the natural immersion potential of the cathode body by including a conductive layer on the surface of the cathode foil.

[0025] The present invention is based on the above-mentioned findings, and in order to solve the above-mentioned problems of electrolytic capacitors for medium and high voltage applications above 100V, especially electrolytic capacitors for medium and high voltage applications above 160V, and more specifically above 250V, the cathode body of the electrolytic capacitor of the present invention is a cathode body of an electrolytic capacitor, characterized in that it includes: a cathode foil of a valve-acting metal, and a conductive layer formed on the surface of the cathode foil, and when a current flows within the current density range of the leakage current of the electrolytic capacitor due to electrochemical polarization, the potential corresponding to the current is higher than the natural immersion potential of a control cathode foil of the same type as the valve-acting metal and with a purity of 99.99% or more.

[0026] Through electrochemical polarization, the current density of the leakage current of the electrolytic capacitor can be in the range of 0.1 μA cm -2 Above 0.3μAcm -2 the following.

[0027] When a current within the current density range of a leakage current of an electrolytic capacitor flows due to electrochemical polarization, if the electrolyte solution contains a nitro compound, the potential corresponding to the current may be 0.15 V or more higher than the natural immersion potential of the reference cathode foil.

[0028] When a current within the current density range of the leakage current of the electrolytic capacitor flows due to electrochemical polarization, the potential corresponding to the current may be 0.3 V or more higher than the natural immersion potential of the reference cathode foil if the electrolyte does not contain a nitro compound.

[0029] In the polarization curve, the range of current density of the leakage current of the electrolytic capacitor may correspond to a potential range in which the current generated by the cathode reaction of reducing dissolved oxygen in the electrolyte is larger than the current generated by the cathode reaction of reducing hydrogen ions.

[0030] The valve action metal may be aluminum.

[0031] The reference cathode foil may be formed with a natural oxide film.

[0032] An electrolytic capacitor including the cathode body is also an aspect of the present invention. The electrolytic capacitor may include: a capacitor element including an anode body having a dielectric oxide film formed thereon and the cathode body; and an electrolyte and a nitro compound filled in the capacitor element.

[0033] [Effects of the Invention]

[0034] According to the present invention, the generation of hydrogen gas can be suppressed simply by adjusting the potential of the cathode body. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The cathode body of Example 1 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte solution containing no nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0036] Figure 2 0.001 μA·cm when the cathode body of Example 1 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing no nitro compound -2 Polarization curves in the range above.

[0037] Figure 3 The cathode body of Example 1 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0038] Figure 4 0.001 μA·cm when the cathode body of Example 1 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound -2 Polarization curves in the range above.

[0039] Figure 5 The cathode body of Example 2 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte solution containing no nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0040] Figure 6 0.001 μA·cm when the cathode body of Example 2 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing no nitro compound -2 Polarization curves in the range above.

[0041] Figure 7 The cathode body of Example 2 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0042] Figure 8 0.001 μA·cm when the cathode body of Example 2 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound -2 Polarization curves in the range above.

[0043] Fig. 9 The cathode body of Example 3 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte solution containing no nitro compound and the concentration of 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0044] Fig.10 0.001 μA·cm when the cathode body of Example 3 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing no nitro compound -2 Polarization curves in the range above.

[0045] Fig.11 The cathode body of Example 3 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0046] Fig.12 0.001 μA·cm when the cathode body of Example 3 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound -2 Polarization curves in the range above.

[0047] Fig.13 The cathode body of Example 4 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte solution containing no nitro compound and the concentration of 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0048] Fig.14 0.001 μA·cm when the cathode body of Example 4 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing no nitro compound -2 Polarization curves in the range above.

[0049] Fig.15 The cathode body of Example 4 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0050] Fig.16 0.001 μA·cm when the cathode body of Example 4 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound -2 Polarization curves in the range above.

[0051] Fig.17 The cathode body of Example 5 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte solution containing no nitro compound and the concentration of 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0052] Fig.18 0.001 μA·cm when the cathode body of Example 5 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing no nitro compound -2 Polarization curves in the range above.

[0053] Fig.19 The cathode body of Example 5 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0054] Fig. 20 0.001 μA·cm when the cathode body of Example 5 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound -2 Polarization curves in the range above.

[0055] Fig.21 The cathode body of Example 6 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte solution containing no nitro compound and the concentration of 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0056] Fig. 22 0.001 μA·cm when the cathode body of Example 6 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing no nitro compound -2 Polarization curves in the range above.

[0057] Fig.23 The cathode body of Example 6 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound and the concentration was 0 or more and 0.4 μA·cm -2 Polarization curves for the following ranges.

[0058] Fig.24 0.001 μA·cm when the cathode body of Example 6 and the control cathode foil of Comparative Example 1 were immersed in an electrolyte containing a nitro compound -2 Polarization curves in the range above.

[0059] Fig.25 This is a graph showing a time series of changes in the height of the casing before and after the DC voltage is applied to the cathode bodies of Examples 1, 3, and 4 and the control cathode foil of Comparative Example 1 when a DC voltage is applied to generate a leakage current. DETAILED DESCRIPTION

[0060] Hereinafter, a cathode body and an electrolytic capacitor according to an embodiment of the present invention will be described. Note that the present invention is not limited to the embodiment described below.

[0061] (Cathode)

[0062] The cathode body is an electrode disposed on the cathode side of the electrolytic capacitor. Examples of electrolytic capacitors having the cathode body include electrolytic capacitors using an electrolyte solution, a gel electrolyte, or both, and so-called hybrid electrolytic capacitors using a solid electrolyte containing a conductive polymer and an electrolyte solution or a gel electrolyte.

[0063] The cathode body includes a cathode foil made of valve metal. The cathode foil is a current collector, and when assembled into an electrolytic capacitor, it is connected to the lead terminal using various methods such as cold welding or pin connection. Valve metals include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony. The purity of the cathode foil is ideally above 99%, and it may also contain impurities such as silicon, iron, copper, magnesium, and zinc. Furthermore, it is preferred to expand the surface of the cathode foil to set the purity of the cathode foil surface to above 99.99%.

[0064] For example, as the cathode foil, aluminum materials with a temper code of H as specified in Japanese Industrial Standard (JIS) H0001, so-called H materials, and aluminum materials with a temper code of O as specified in JIS H0001, so-called O materials, can be used. If a metal foil with high rigidity including H materials is used, deformation of the cathode foil due to press working can be suppressed.

[0065] The valve metal of the cathode foil is extended in foil shape. The surface of the cathode foil can be subjected to a surface expansion treatment. The surface expansion layer of the cathode foil is formed by electrolytic etching, chemical etching, sandblasting, etc., or is formed by evaporating or sintering metal particles on the metal foil. As electrolytic etching, methods such as DC etching or AC etching can be listed. In addition, in chemical etching, the metal foil is immersed in an acid solution or an alkaline solution. The formed surface expansion layer is a layer area having tunnel-shaped etching pits or sponge-shaped etching pits engraved from the foil surface to the foil core. Furthermore, the etching pits can also be formed in a way that penetrates the cathode foil.

[0066] An oxide film may be formed intentionally or naturally on the expanded surface layer. A natural oxide film is formed by the reaction of the cathode foil with oxygen in the air, and a chemical conversion film is an oxide film intentionally formed by a chemical conversion treatment in which a voltage is applied in a solution such as an aqueous solution of adipic acid or boric acid without halogen ions. In the case where the metal foil is, for example, aluminum foil, the oxide film obtained by the above method is aluminum oxide formed by oxidation of the expanded surface layer.

[0067] The cathode body has a laminated structure of a cathode foil and a conductive layer. The conductive layer contains a conductive material and is a layer with higher conductivity than the oxide film. The conductive layer is laminated on one or both sides of the cathode foil and is located on the outermost layer of the cathode body. Examples of the conductive material include carbon materials, titanium, titanium nitride, titanium carbide, aluminum carbide, and composite materials or mixed materials thereof. The conductive layer may be laminated with multiple layers.

[0068] The carbon material is fibrous carbon, carbon powder, or a mixture of these. It can also be fibrous carbon or carbon powder that has been subjected to a porous treatment such as activation treatment or opening treatment to form holes. Carbon powder is, for example, activated carbon derived from natural plant tissues such as coconut shells, synthetic resins such as phenol, coal, coke, asphalt and other fossil fuels, ketjen black, acetylene black, channel black and other carbon blacks, carbon nanohorns, amorphous carbon, natural graphite, artificial graphite, graphitized ketjen black, mesoporous carbon, etc. Fibrous carbon is, for example, carbon nanotubes, carbon nanofibers, etc. Carbon nanotubes can be single-layer carbon nanotubes with one layer of graphene sheets, or multi-layer carbon nanotubes (MWCNT) with two or more layers of graphene sheets curled coaxially and multiple layers of tube walls.

[0069] These conductive materials are attached to the cathode foil by coating, evaporation or heat treatment. The coating method is suitable for forming a conductive layer of carbon material, for example, by applying a slurry containing a conductive material, a binder and a solvent to the cathode body by a slurry casting method, a doctor blade method or a spray method and drying it, and the cathode foil and the conductive layer are closely connected by pressing as needed. The evaporation method is suitable for forming a conductive layer of a metal system such as titanium, for example, vacuum arc evaporation, sputtering evaporation or electron beam evaporation can be cited. The heat treatment is to make the powder of the conductive material adhere to the surface of the cathode foil and sinter it.

[0070] Vacuum arc evaporation is to apply voltage to a material source in a vacuum chamber to melt and evaporate it, so that the evaporated material source reacts with the reaction gas, and the material source that reacts with the reaction gas is formed into a film on the cathode foil. Sputtering evaporation is to generate plasma in an environment where a target is configured and filled with a reaction gas, and the material source is knocked from the target while reacting with the reaction gas, so that the material source that reacts with the reaction gas is formed into a film on the cathode foil. Electron beam evaporation is to irradiate an electron beam to a material source in a vacuum chamber to melt and evaporate it, so that the evaporated material source reacts with the reaction gas, and the material source that reacts with the reaction gas is formed into a film on the cathode foil.

[0071] Here, the cathode body is adjusted so that when a current within the current density range of the leakage current of the electrolytic capacitor flows, the potential corresponding to the current is higher than the natural immersion potential of the reference cathode foil. The reference cathode foil is a comparison object with respect to the natural immersion potential of the cathode body. The reference cathode foil is a foil containing the same valve action metal as the cathode foil of the cathode body, and has a purity of 99.99% or more.

[0072] The potential corresponding to the current within the current density range of the leakage current of the electrolytic capacitor can be confirmed by the polarization curve while adjusting the conductive layer formed on the cathode foil, for example. The cathode body and the reference cathode foil are respectively set as working electrodes, and the silver-silver chloride electrode is set as the reference electrode, and the natural immersion potential of the reference cathode foil and the polarization curve of the cathode body are measured. Then, by adjusting, for example, the coverage rate of the conductive layer relative to the cathode foil, the surface area of ​​the conductive layer, or the constituent material or content ratio of the conductive layer, the potential range relative to the current density range of the leakage current can be closer to the high side than the natural immersion potential of the reference cathode foil.

[0073] The reference cathode foil is formed with a natural oxide film and has a natural immersion potential at which a cathode reaction that preferentially reduces hydrogen ions occurs. On the other hand, the cathode body has a natural immersion potential higher than that of the reference cathode foil within the current density range of the leakage current. That is, the cathode body is located at a higher potential than that at which a cathode reaction that preferentially reduces hydrogen ions occurs within the current density range of the leakage current.

[0074] That is, when leakage current is generated in the electrolytic capacitor, the potential of the cathode body is higher than the potential for generating the cathode reaction of reducing hydrogen ions, and is in a potential range where the cathode reaction of reducing dissolved oxygen as shown in the following chemical reaction formula (4) is preferentially generated. Therefore, in the cathode body, the cathode reaction of reducing hydrogen ions is suppressed, and the generation of hydrogen gas is suppressed.

[0075] O2+2H2O+4e - →4OH - …(4)

[0076] Preferably, when the electrolyte contains a nitro compound, the potential of the cathode body when the leakage current flows is set to a higher side of 0.15V or more than the natural immersion potential of the reference cathode foil. If it is set to a higher side of 0.15V or more, the effect of suppressing hydrogen generation by the cathode body becomes particularly good compared with the amount of hydrogen generated in the reference cathode foil. In addition, when the electrolyte does not contain a nitro compound, the potential of the cathode body when the leakage current flows is set to a higher side of 0.3V or more than the natural immersion potential of the reference cathode foil. If it is set to a higher side of 0.3V or more, the effect of suppressing hydrogen generation by the cathode body becomes particularly good compared with the amount of hydrogen generated in the reference cathode foil.

[0077] Here, the potential corresponding to the leakage current range can also be adjusted using the natural immersion potential of the cathode body as an indicator. By adjusting the natural immersion potential of the cathode body to be higher than the natural immersion potential of the reference cathode foil, the potential corresponding to the leakage current range can be higher than the natural immersion potential of the reference cathode foil. The natural immersion potential of the cathode body is adjusted, for example, by the coverage of the conductive layer relative to the cathode foil, the surface area of ​​the conductive layer, or the constituent material or content ratio of the conductive layer.

[0078] The natural impregnation potential of the cathode body is preferably set to be higher than the natural impregnation potential of the reference cathode foil by 0.4 V or more. With respect to the cathode body having a natural impregnation potential higher than the natural impregnation potential of the reference cathode foil by 0.4 V or more, when leakage current flows, the cathode reaction of reducing dissolved oxygen accounts for the majority, and the cathode reaction of reducing hydrogen is greatly suppressed, and the effect of suppressing hydrogen generation becomes particularly good compared with the amount of hydrogen generated in the reference cathode foil.

[0079] By setting it to be 0.4 V or more higher than the natural immersion potential of the control cathode foil, when the electrolyte contains a nitro compound, the potential when the leakage current flows can be ensured to be 0.15 V or more higher than the natural immersion potential of the control cathode foil, and the effect of suppressing hydrogen generation becomes particularly good compared with the amount of hydrogen generated in the control cathode foil.

[0080] In addition, by setting it to a high side of 0.4 V or more higher than the natural immersion potential of the control cathode foil, when the electrolyte does not contain nitro compounds, the potential when the leakage current flows can be ensured to be a high side of 0.3 V or more higher than the natural immersion potential of the control cathode foil, and the effect of suppressing hydrogen generation becomes particularly good compared with the amount of hydrogen generated in the control cathode foil.

[0081] It is further preferred that the conductive layer contains a carbon component, and the natural immersion potential of the cathode body is set to be higher than the natural immersion potential of the reference cathode foil by more than 0.6V. The so-called inclusion of a carbon component means that in addition to the carbon material itself contained in the conductive layer, a conductive material containing carbon atoms in the molecular structure such as titanium carbide is also contained in the conductive layer. In the case where the conductive layer contains a carbon component, within the range where the difference between the natural immersion potential of the cathode body and the natural immersion potential of the reference cathode foil is less than 0.6V, the closer the difference is to 0.6V, the shorter the duration of the inhibitory effect of hydrogen generation becomes. However, in the case where the conductive layer contains a carbon component, the difference between the natural immersion potential of the cathode body and the natural immersion potential of the reference cathode foil is limited to 0.6V, and the duration of the inhibitory effect of hydrogen generation suddenly increases sharply, and a longer hydrogen generation inhibitory effect can be obtained in the range less than 0.6V.

[0082] Regarding the above cathode body, the cathode body is set as the working electrode and the silver-silver chloride electrode is set as the reference electrode. When measuring the polarization curve, the natural immersion potential is higher than the natural immersion potential of the control cathode foil, and the polarization curve is drawn by the area formed by the potential range in which the cathode reaction of reducing dissolved oxygen is more preferentially generated and the cathode reaction of reducing hydrogen ions is weak and the current range in which the leakage current of the electrolytic capacitor is generated.

[0083] The general range of the current density of the leakage current of the electrolytic capacitor is 0.1 μA cm -2 Above 0.3μAcm -2 the following.

[0084] (Electrolytic Capacitors)

[0085] The electrolytic capacitor is formed by accommodating the capacitor element including the cathode body in a shell and sealing the shell opening with a sealing body. The shell is made of aluminum, an aluminum alloy containing aluminum or manganese, or a stainless steel product, and is a cylinder with a bottom and an opening at the other end. The shell is riveted, the opening of the shell is bent inward and flattened, and the sealing body is closely connected. The sealing body is formed, for example, of a resin plate containing a resin such as a phenolic resin or an elastic body such as rubber.

[0086] The capacitor element includes an anode body and a separator in addition to a cathode body. In addition, the capacitor element includes an electrolyte filled in the gaps in the capacitor element or in the separator. The anode body has a dielectric oxide film on the surface. The electrolyte is between the anode body and the cathode body and is in close contact with the dielectric oxide film.

[0087] (Anode)

[0088] The anode body is formed by forming a dielectric oxide film on the surface of an anode foil made of a valve metal. The valve metal is aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, etc. The purity of the anode foil is preferably 99.9% or more, but it may contain impurities such as silicon, iron, copper, magnesium, zinc, etc.

[0089] The anode foil is a formed body formed by forming a powder of a valve metal, a sintered body formed by sintering the formed body, or an etched foil formed by etching a rolled foil, and the surface is expanded. The expanded surface structure includes tunnel-shaped pits, sponge-shaped pits, or gaps between dense powders. Typically, the expanded surface structure is formed by applying direct current or alternating current to an acidic aqueous solution containing halogen ions such as hydrochloric acid, or by evaporating or sintering metal particles on the core. The cathode foil can also have an expanded surface structure by etching.

[0090] The dielectric oxide film is typically an oxide film formed on the surface of the anode foil. For example, if the anode foil is an aluminum foil, the dielectric oxide film is aluminum oxide formed by oxidizing the expanded surface structure. The dielectric oxide film is formed by chemical conversion treatment in an aqueous solution of adipic acid, boric acid or phosphoric acid, etc. In addition, a thin dielectric oxide film (about 1V to 10V) can be formed on the surface of the cathode foil by chemical conversion treatment as needed. Furthermore, the dielectric oxide film can also be made using a vapor deposition method, a sol-gel method, or a liquid phase precipitation method.

[0091] (Partition)

[0092] Examples of the separator include cellulose such as kraft, Manila hemp, esparto, hemp, rayon, and mixed papers thereof, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, polyamide resins such as aliphatic polyamides, semi-aromatic polyamides, and wholly aromatic polyamides, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, polyvinyl alcohol resins, and the like. These resins may be used alone or in combination.

[0093] (Electrolytes)

[0094] In the case of an electrolytic capacitor using an electrolyte, the electrolyte is an electrolyte obtained by dissolving a solute in a solvent and adding additives as needed. The solvent may be any of a protic polar solvent or an aprotic polar solvent. As protic polar solvents, monohydric alcohols, polyhydric alcohols, oxyalcohol compounds, water, etc. can be cited as representatives. As aprotic polar solvents, sulfone series, amide series, lactone series, cyclic amide series, nitrile series, oxide series, etc. can be cited as representatives.

[0095] The solute contained in the electrolyte contains components of anions and cations, typically an organic acid or its salt, an inorganic acid or its salt, or a composite compound of an organic acid and an inorganic acid or a salt having ion dissociation thereof, which can be used alone or in combination of two or more. An acid that becomes an anion and a base that becomes a cation can also be added to the electrolyte as solute components.

[0096] Furthermore, other additives may be added to the electrolyte. Examples of additives include polyethylene glycol, complex compounds of boric acid and polysaccharides (mannitol, sorbitol, etc.), complex compounds of boric acid and polyols, boric acid esters, nitro compounds, phosphate esters, colloidal silica, etc. These may be used alone or in combination of two or more. Nitro compounds suppress the generation of hydrogen in the electrolytic capacitor. Examples of nitro compounds include o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, etc.

[0097] In the case of using a solid electrolyte in an electrolytic capacitor, it is sufficient as long as a conjugated polymer or a doped conjugated polymer, i.e., a conductive polymer, is contained in the electrolyte layer. As a conjugated polymer, a known conjugated polymer can be used without particular limitation. As the conjugated polymer, for example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylene vinylene, polyphenylene, polythiophene vinylene, etc., preferably poly (3,4-ethylenedioxythiophene) etc. These conjugated polymers can be used alone, or two or more can be combined, or they can be copolymers of two or more monomers.

[0098] When a gel electrolyte is used in an electrolytic capacitor, polyvinyl alcohol may be added to the electrolyte to increase its viscosity, or the electrolyte may be composed of an electrolyte and a polymer that maintains a three-dimensional network structure of the electrolyte. The polymer of the three-dimensional network structure is formed by polymerizing the monomer using a monomer that is the main chain of the gel network, a polymerization initiator for polymerizing the monomer, and a cross-linking agent for cross-linking the polymer, and cross-linking the polymer.

[0099] [Example]

[0100] Hereinafter, the cathode body and the electrolytic capacitor of the present invention will be described in more detail based on examples. Note that the present invention is not limited to the examples described below.

[0101] (Example 1 to Example 6)

[0102] Cathode bodies of Examples 1 to 6 and a control cathode foil of Comparative Example 1 shown in Table 1 below were produced.

[0103] [Table 1]

[0104]

[0105] As shown in Table 1, the cathode foils included in the cathode bodies of Examples 1 to 6 and the control cathode foil of Comparative Example 1 are aluminum foils of the same shape and size. The cathode foils of Examples 1 to 3 and Example 5 and Comparative Example 1 are formed with an expanded surface layer by etching. The cathode foils of Examples 4 and 6 do not have an expanded surface layer.

[0106] In addition, on the surface of the cathode foil of Example 1, a conductive layer containing carbon black as a carbon material is laminated by a coating method, and after lamination, the cathode body of Example 1 is press-formed. On the surface of the cathode foil of Example 2, a conductive layer containing titanium nitride is laminated by a vacuum arc evaporation method. On the surface of the cathode foil of Example 3, a conductive layer containing titanium carbide is laminated by a vacuum arc evaporation method. On the surface of the cathode foil of Example 4, a conductive layer having a two-layer structure of a lower base layer containing titanium and an upper base layer of a carbon material is formed by a sputtering evaporation method. On the surface of the cathode foil of Example 5, the surface of the aluminum foil is carbonized by heat treatment, and then coated with titanium oxide powder, thereby forming a conductive layer having a two-layer structure of aluminum carbide and titanium oxide. On the surface of the cathode foil of Example 6, a conductive layer containing titanium nitride is laminated by an electron beam evaporation method.

[0107] Furthermore, regarding the cathode bodies of Examples 1 to 6, referring to the polarization curve, the potential corresponding to the leakage current range of the electrolytic capacitor exceeds the natural immersion potential of the control cathode foil of Comparative Example 1. The polarization curve was measured using a three-electrode method. Specifically, each cathode body and the control cathode foil were cut into a size of 2 cm × 5 cm and used as working electrodes, the reference electrode was set as a silver-silver chloride electrode, and the counter electrode was set as a SUS304 stainless steel mesh, and these electrodes were immersed in an electrolyte. The dissolved oxygen concentration of the electrolyte was adjusted to 0.4 mg / L -1 ~1.0mgL -1 Each electrode was connected to a potentiostat, and after the natural immersion potential was stabilized, the value of the natural immersion potential was obtained. After the natural immersion potential was stabilized, polarization was performed from the natural immersion potential to -1.7 V in units of 50 mV. Each potential at 50 mV intervals was maintained for 10 minutes, and the average current value of the last minute was measured.

[0108] The polarization curves of the cathode bodies of Examples 1 to 8 with the potential adjusted are shown in Figures 1 to 24 Figure (4n-3) is a graph showing the natural immersion potential above 0 and 0.4 μA·cm -2 The following polarization curves are shown when the cathode body of Example n (n=1, 2, 3, etc.) is immersed in an electrolyte solution containing no nitro compound within the current density range. -2The polarization curves when the cathode body of Example n (n=1, 2, 3, etc.) is immersed in an electrolyte solution containing no nitro compound are shown in the above current density range. In addition, Figure (4n-1) is a graph of the natural immersion potential at 0 or above and 0.4 μA·cm -2 The following polarization curves are shown when the cathode body of Example n (n=1, 2, 3, etc.) is immersed in an electrolyte containing a nitro compound within the current density range. -2 Polarization curves are shown when the cathode body of Example n (n=1, 2, 3, etc.) is immersed in an electrolyte containing a nitro compound within the above current density range. In Figures (4n-3) and (4n-2), polarization curves of the control cathode foil of Comparative Example 1 related to an electrolyte not containing a nitro compound are also recorded, and in Figures (4n-1) and (4n), polarization curves of the control cathode foil of Comparative Example 1 related to an electrolyte containing a nitro compound are also recorded.

[0109] In the polarization curves of Figure (4n-3) and Figure (4n-1), the leftmost plot is the natural immersion potential. Figures 1 to 24 As shown in the figure, it can be confirmed that the cathode bodies of Examples 1 to 6 have a leakage current density range of 0.1 μA cm -2 Above 0.3μAcm -2 In the following ranges, the potential is higher than the natural immersion potential of the reference cathode foil of Comparative Example 1.

[0110] Electrolytic capacitors are manufactured using the cathode bodies of Examples 1 to 6 and the control cathode foils of Comparative Example 1. The electrolytic capacitors are identical except for the cathode bodies and the control cathode foils. Aluminum foil can be used as the anode body of each electrolytic capacitor to form a surface expansion layer and further form a dielectric oxide film. A kraft paper partition is sandwiched between the cathode body and the anode body, and the stack of the anode body, the partition and the cathode body is wound. The wound body is impregnated with an electrolyte to complete the capacitor element. The electrolyte is prepared by adding azelaic acid to ethylene glycol. Two types of electrolytes are provided, and p-nitrobenzyl alcohol is added as a nitro compound to one of the electrolytes at a ratio of 2wt%. The capacitor element is housed in an aluminum casing and sealed with a sealing body.

[0111] A DC voltage of 450 V was applied to the electrolytic capacitors of Examples 1 to 6 and Comparative Example 1 for 2000 hours at a temperature of 105°C, generating a current density of 0.1 μA cm -2 ~0.3μAcm -2The amount of hydrogen generated is measured by measuring the height of the shell before and after the application of the DC voltage, and is measured based on the difference in height before and after the application. As a method for evaluating the amount of hydrogen generated, it is divided into three categories: large hydrogen generation, medium hydrogen generation, and small hydrogen generation. The shell expansion ratio of the electrolytic capacitor of Comparative Example 1 is classified as large hydrogen generation and used as a benchmark. The classification to which Examples 1 to 6 belong is determined by relative evaluation based on Comparative Example 1.

[0112] The measurement results of the amount of hydrogen generated in Examples 1 to 6 and Comparative Example 1 are shown in Table 2 below. In the table, the amount of hydrogen generated is indicated by ×, △, and ○. The × mark indicates that the shell of the electrolytic capacitor expands greatly, the amount of hydrogen generated is large, and there is no hydrogen suppression effect. The △ mark indicates that the shell of the electrolytic capacitor expands moderately, the amount of hydrogen generated is moderate, and there is a hydrogen suppression effect. The ○ mark indicates that the shell of the electrolytic capacitor expands slightly, the amount of hydrogen generated is small, and the hydrogen suppression effect is large. The natural immersion potential is also recorded in Table 2.

[0113] [Table 2]

[0114]

[0115] As shown in Table 2, when the amount of hydrogen generated was measured, it was confirmed that the amount of hydrogen generated by the electrolytic capacitors including the cathode bodies of Examples 1 to 6 was less than that of the electrolytic capacitor including the control cathode foil of Comparative Example 1, and a hydrogen suppression effect was produced compared with Comparative Example 1. That is, it was confirmed that the cathode body whose potential with respect to the leakage current range was higher than the natural immersion potential of the control cathode foil exerted the effect of suppressing hydrogen.

[0116] In particular, for the electrolytic capacitors including the cathode bodies of Example 1, Example 5 and Example 6, even when an electrolyte solution containing no nitro compound is used, a high hydrogen suppression effect is produced. In the polarization curves of Figure (4n-3) and Figure (4n-2), if the potential range corresponding to the leakage current range is compared, the potential range corresponding to the leakage current range in the polarization curves of Example 1, Example 5 and Example 6 is greater than that in the Figure 1 , Figure 2 , Fig.17 , Fig.18 , Fig.21 and Fig. 22 In the results, it was confirmed that a potential higher than the natural immersion potential of the reference cathode foil of Comparative Example 1 was ensured by 0.3 V or more. That is, it was confirmed that the effect of suppressing hydrogen gas was particularly high when the potential relative to the leakage current range was higher than the natural immersion potential of the reference cathode foil by 0.3 V or more under the condition that the electrolyte did not contain a nitro compound.

[0117] In addition, for the electrolytic capacitors including the cathode bodies of Example 1, Example 5 and Example 6, even when an electrolyte containing a nitro compound is used, a high hydrogen suppression effect is produced. In the polarization curves of Figure (4n-1) and Figure (4n), if the potential range corresponding to the leakage current range is compared, in the polarization curves of Example 1, Example 5 and Example 6, the potential range corresponding to the leakage current range is 0.04477 W / m. Figure 3 , Figure 4 , Fig.19 , Fig. 20 , Fig.23 and Fig.24 In the results, it was confirmed that a potential higher than the natural immersion potential of the reference cathode foil of Comparative Example 1 was ensured by 0.15 V or more. That is, it was confirmed that the effect of suppressing hydrogen gas by the cathode body whose potential relative to the leakage current range was higher than the natural immersion potential of the reference cathode foil by 0.15 V or more was particularly high under the condition that the electrolyte contained a nitro compound.

[0118] Furthermore, as shown in Table 2, in the cathode bodies of Examples 1 to 6 in which the potential corresponding to the leakage current was higher than the natural immersion potential of the reference cathode foil, the natural immersion potential was also higher than the natural immersion potential of the reference cathode foil.

[0119] In the case where the electrolyte contains a nitro compound, the natural immersion potentials of the cathode bodies of Examples 1, 5, and 6, which are 0.15 V or more higher than the natural immersion potential of the comparative cathode foil of Comparative Example 1, are 0.4 V or more higher than the natural immersion potential of the comparative cathode foil of Comparative Example 1. In addition, in the case where the electrolyte does not contain a nitro compound, the natural immersion potentials of the cathode bodies of Examples 1, 5, and 6, which are 0.3 V or more higher than the natural immersion potential of the comparative cathode foil of Comparative Example 1, are 0.6 V or more higher than the natural immersion potential of the comparative cathode foil of Comparative Example 1.

[0120] Furthermore, as shown by the ○ mark and the △ mark in Table 2, it can be confirmed that the hydrogen suppression effect of Example 1 is greater than that of Example 3 and Example 4. In Example 1, Example 3 and Example 4, a carbon component is contained in the conductive layer. Specifically, in Example 1, carbon itself is contained in the conductive layer as a carbon component, in Example 3, titanium carbide containing carbon atoms is contained in the conductive layer as a carbon component, and in Example 4, a lower base layer of titanium and an upper base layer of carbon material are contained in the conductive layer as carbon components. Moreover, as shown in Table 2, with respect to the difference in natural immersion potential with Comparative Example 1 as a control electrode, Example 1 is 0.6V or more and about 0.71V, Example 3 is about 0.42V, and Example 4 is about 0.56V.

[0121] The results of Table 2 are shown in Fig.25 Graph of the curve. Fig.25 It means that the current density is 0.1 μA cm when a DC voltage of 450 V is applied for 2000 hours at a temperature of 105°C. -2 ~0.3μAcm -2 A graph showing the time series of the change in the height of the housing before and after the DC voltage is applied when the leakage current is applied.

[0122] like Fig.25 As shown in the figure, when comparing Example 3 and Example 4, in which the difference in natural immersion potential with Comparative Example 1 as the control electrode is less than 0.6V, the shell height change ΔL of Example 3 is smaller than that of Example 4, and the generation of hydrogen is less. Specifically, not only Example 3 but also Example 4 did not change the shell height change ΔL before 1000 hours after voltage application, and almost no hydrogen was generated, but after 1000 hours, a change was observed in the shell height change ΔL. Among them, the shell height change ΔL of Example 4 became steeper than the shell height change ΔL of Example 3.

[0123] Here, the difference between the natural immersion potential of Example 3 and Comparative Example 1 as the reference electrode is 0.42 V, and the difference between the natural immersion potential of Example 4 and Comparative Example 1 as the reference electrode is 0.56 V. Based on the results of Examples 3 and 4, it can be confirmed that within the range where the difference between the natural immersion potential of Comparative Example 1 as the reference electrode is less than 0.6 V, the closer the difference between the natural immersion potential of Comparative Example 1 as the reference electrode is to 0.6 V, the shorter the duration of hydrogen suppression becomes.

[0124] On the other hand, Fig.25 As shown in the figure, in Example 1, in which the difference in natural immersion potential from Comparative Example 1 as the reference electrode was 0.6 V or more, even after 2000 hours, which was more than 1000 hours, from the start of voltage application, the change in height ΔL of the shell did not change, and the amount of hydrogen generation was continuously suppressed. That is, it can be seen that if the difference in natural immersion potential from Comparative Example 1 as the reference electrode was 0.6 V or more, the persistence of the hydrogen suppression effect suddenly increased sharply.

[0125] As described above, it was confirmed that the smaller the difference in the natural immersion potential between the cathode body and the reference electrode, the greater the effect of suppressing hydrogen generation as it approaches 0.6 V, but the duration of the effect becomes shorter. On the other hand, the duration can be rapidly extended with 0.6 V as the limit.

Claims

1. A cathode body, which is a cathode body of an electrolytic capacitor, characterized in that include: Cathode foil of valve metal, and A conductive layer is formed on the surface of the cathode foil, wherein the conductive layer contains a carbon material. When a current within the current density range of the leakage current of the electrolytic capacitor flows due to electrochemical polarization, the potential corresponding to the current is higher than the natural immersion potential of the control cathode foil which is the same type as the valve metal and has a purity of 99.99% or more, When a current within the current density range of the leakage current of the electrolytic capacitor flows due to electrochemical polarization, when the electrolyte contains a nitro compound, the potential corresponding to the current is higher than the natural immersion potential of the reference cathode foil by 0.15 V or more.

2. A cathode body, which is a cathode body of an electrolytic capacitor, characterized in that include: Cathode foil of valve metal, and A conductive layer is formed on the surface of the cathode foil, wherein the conductive layer contains a carbon material. When a current within the current density range of the leakage current of the electrolytic capacitor flows due to electrochemical polarization, the potential corresponding to the current is higher than the natural immersion potential of the control cathode foil which is the same type as the valve metal and has a purity of 99.99% or more, When a current within the current density range of the leakage current of the electrolytic capacitor flows due to electrochemical polarization, the potential corresponding to the current is higher than the natural immersion potential of the reference cathode foil by 0.3 V or more when the electrolyte does not contain a nitro compound.

3. The cathode body according to claim 1 or 2, characterized in that Through electrochemical polarization, the current density of the leakage current of the electrolytic capacitor is in the range of 0.1 μA cm -2 Above 0.3μAcm -2 the following.

4. The cathode body according to claim 1 or 2, characterized in that In the polarization curve, the range of the current density of the leakage current of the electrolytic capacitor corresponds to a potential range in which the current generated by the cathode reaction of reducing dissolved oxygen in the electrolyte is larger than the current generated by the cathode reaction of reducing hydrogen ions.

5. The cathode body according to claim 1 or 2, characterized in that The valve action metal is aluminum.

6. The cathode body according to claim 1 or 2, characterized in that The cathode foil has a natural oxide film formed thereon.

7. An electrolytic capacitor comprising the cathode body according to any one of claims 1 to 6.

8. The electrolytic capacitor according to claim 7, characterized in that include: A capacitor element comprising an anode body formed with a dielectric oxide film and the cathode body; as well as The capacitor element is filled with an electrolyte and a nitro compound.